The Influence of Technological Progress on Regional Income Inequality in Indonesia - Nur Sholeh, Achmad; Nizar, nefo Indra; Nazir, ahmad (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2023)
The aim of this research is to determine the influence of technology on regional economic development as well as prove whether technology can cause income inequality in Indonesia. This research method uses panel data regression estimation. Panel data is a combination of cross section and time series data. Meanwhile, a technology index was calculated based on indicators of smartphone, internet and computer use to see the characteristics of the technological dimensions of each province in Indonesia. The data used is secondary data from provinces throughout Indonesia for the 2016-2022 time period. The data source was taken from the Indonesian Central Statistics Agency. The panel data regression estimation results are estimated smartphone owners ratio and computer user rasio do not affect regional income inequality significantly meanwhile internet access rasio affect regional income inequality partially. All variables affected regional Income simultaneously or tecnological progress has affected regional income inequality in Indonesia.